2018
DOI: 10.1159/000494482
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of N-Acetylglucosaminyltransferase GCNT3 by miR-302b-3p Decreases Non-Small Cell Lung Cancer (NSCLC) Cell Proliferation, Migration and Invasion

Abstract: Background/Aims: GCNT3 is a member of N-acetylglucosaminyltransferase family involved with mucin biosynthesis. GCNT3 aberrant expression is known to promote the progression of several human cancers. However, its role in tumorigenesis and the progression of non-small cell lung cancer (NSCLC) has not been well-characterized. Our study investigated the functional mechanisms of GCNT3 regulated by microRNAs (miRNAs) in NSCLC. Methods: The differential expression of mRNAs in NSCLC tissues and matched adjacent non-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 51 publications
2
26
0
Order By: Relevance
“…Downregulation of GCNT3 has been earlier shown to reduce invasion and migration in non-small cell lung cancer. 48 Also, Rao et al showed higher incidence of GCNT3 in human pancreatic tissues and 10-month-old Kras-induced genetically engineering mouse model. 30 Higher expression of GCNT3 was associated with poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of GCNT3 has been earlier shown to reduce invasion and migration in non-small cell lung cancer. 48 Also, Rao et al showed higher incidence of GCNT3 in human pancreatic tissues and 10-month-old Kras-induced genetically engineering mouse model. 30 Higher expression of GCNT3 was associated with poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…It mainly includes adenocarcinomas (AD) and squamous cell carcinomas . 3 Despite the latest advancements in NSCLC diagnosis and treatment strategies, the 5-year survival rate of NSCLC patients is approximately 10–15% 4,5. It is critical to identify novel biomarkers and key signaling pathways to develop effective therapeutic, diagnostic, and prognostic strategies for NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that LUAD had high expression of ASPM and ECT2, which both indicated poor prognosis, and ECT2 could facilitate lung tumorigenesis [ 43 49 ]. Lung cancer also has high expression profile of GCNT3 (a gene regulating mucin synthesis), GOLM1(a gene coding for a Golgi transmembrane protein) and IGF2BP3 (a gene coding for a RNA binding protein), which are all positively correlated with malignant progression of lung cancer [ 50 53 ]. Nutrient transporter SLC2A1 and SLC7A5 both exhibit cancer-promoting potential in lung cancer [ 54 56 ].…”
Section: Discussionmentioning
confidence: 99%